Economics and the enforcement of European competition law - Decker, Christopher 1972- (Cheltenham, UK Edward Elgar, 2009)
"This book seeks to place in perspective the growing use of economics in European competition law enforcement by examining precisely how economics contributes to the enforcement activity of the European Commission and Courts.Christopher Decker provides unique empirical insights as to how economic theory, thinking, techniques and data have featured in decision-making in the area of co-ordinated effects. The role of economics is examined throughout the entire enforcement process, from the decision to initiate an investigation to the design and implementation of remedies, and its conclusions are of general relevance to all areas of competition law enforcement where economics is used.Utilising a broad and multifaceted conception of economics, this book is essential reading for academics and students interested in European competition law, EC competition lawyers, applied industrial economists and enforcement officials. It will also be an invaluable tool for academic libraries and institutes, government agencies, law firms and economic consultancies"--Provided by publisher.
Includes bibliographical references (p. 236-276) and index.
Keywords: Antitrust law -- Economic aspects -- European Union countries; Competition, Unfair -- Economic aspects -- European Union countries; Law and economics